Regioselective Synthesis of Oxepin and Oxocin Annulated Quinoline Heterocycles by Ring-Closing Metathesis - Majumdar, Krishna C.; Debnath, Pradip; Taher, Abu (Letters in Organic Chemistry, 2008)
Regioselective synthesis of oxepin and oxocin annulated quinoline heterocycles by the combination of Claisen rearrangement and ring-closing metathesis reaction is described. The ring-closing metathesis (RCM) and ring-closing enyne metathesis (RCEM) proceeded smoothly in the presence of Grubbs' catalyst A or B in toluene under nitrogen atmosphere without deactivation of the basic quinoline nitrogen.
Keywords: Ring-closing metathesis